A case of unresolved skin lesion in a cobbler - Mert, Ali; Kaya, Abdurrahman; Yıldız Kaya, Sibel (My University, 2024)
[Abstract Not Available]
Un caso de lesión cutánea no resuelta en un zapatero
Keywords: Antibiotic Agent; C Reactive Protein; Hemoglobin